2007
DOI: 10.1080/03670240701486743
|View full text |Cite
|
Sign up to set email alerts
|

Subsistence and Food Sharing in Northern Siberia: Social and Nutritional Ecology of the Dolgan and the Nganasan

Abstract: Traditional foraging activities and extensive food sharing are critical to the contemporary nutritional well-being of Dolgan and Nganasan people in the Taimyr Region, Russia. Despite recent economic transformations geared toward free-market capitalism in the post-socialist era, since 1991, a native communal resource-management regime has developed. This article outlines the social and nutritional significance of subsistence and food sharing within a remote indigenous community in Arctic Siberia. Empirical data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…Taken together, his answer reveals that durable and possibly reciprocal ties to specific others do exist even as demands for unconditional sharing are present. This example is consistent with many recent studies that have also reported high levels of reciprocity in comparable situations (Allen-Arave et al 2008 ; Gurven 2004 ; Gurven et al 2000 ; Koster 2011 ; Nolin 2010 ; Wiessner 2005 :136; Ziker 2007 ).…”
supporting
confidence: 91%
“…Taken together, his answer reveals that durable and possibly reciprocal ties to specific others do exist even as demands for unconditional sharing are present. This example is consistent with many recent studies that have also reported high levels of reciprocity in comparable situations (Allen-Arave et al 2008 ; Gurven 2004 ; Gurven et al 2000 ; Koster 2011 ; Nolin 2010 ; Wiessner 2005 :136; Ziker 2007 ).…”
supporting
confidence: 91%
“…Households that share in Ifaluk are more closely related than the population on average (Betzig and Turke 1986). Kinship is a strong predictor of between-household sharing in the Iñupiaq communities of Deering and Wales, Alaska (Madganz et al 2002), the Dolgan/Nganasan village of Ust’-Avam, Siberia (Ziker and Schnegg 2005, Ziker 2007), and the Achuar/Quichua community of Conambo, Ecuador (Patton 2005). Sharing among the Ache shows considerable kin-bias on the reservation (Gurven et al 2001), but this appears to be due to preferential reciprocal exchange with kin, rather than need-based sharing directed towards kin (Allen-Arave et al 2008).…”
Section: Theories Of Food Sharingmentioning
confidence: 99%
“…Knowledge of food sharing and the sexual division of labor in huntergatherers is mostly based on the distribution of foods at central places (e.g. Ziker, 2007;Kitanishi, 1998;Bahuchet, 1990), or in mixed-sex or single sex groups (e.g. Kaplan et al, 1984;Ziker, 2002).…”
Section: Introductionmentioning
confidence: 99%